2017
DOI: 10.1038/srep43914
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of steroid-induced osteonecrosis of the femoral head using porous Se@SiO2 nanocomposites to suppress reactive oxygen species

Abstract: Reducing oxidative stress (ROS) have been demonstrated effective for steroid-induced osteonecrosis of the femoral head (steroid-induced ONFH). Selenium (Se) plays an important role in suppressing oxidative stress and has huge potential in ONFH treatments. However the Se has a narrow margin between beneficial and toxic effects which make it hard for therapy use in vivo. In order to make the deficiency up, a control release of Se (Se@SiO2) were realized by nanotechnology modification. Porous Se@SiO2 nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…BMSCs are used to treat early steroid-induced ONFH [43][44][45] ; their survival and stemness in the bone necrotic area are key to the effectiveness of transplantation 46,47 . Studies have revealed an OS microenvironment in the femoral-head necrotic area in which transplanted BMSCs incur a great deal of stress apoptosis and aging, which seriously limits transplantation effectiveness [11][12][13] . More and more studies have shown that mitochondrial dysfunction and damaged-mitochondria accumulation occur before cell stress apoptosis and senescence [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BMSCs are used to treat early steroid-induced ONFH [43][44][45] ; their survival and stemness in the bone necrotic area are key to the effectiveness of transplantation 46,47 . Studies have revealed an OS microenvironment in the femoral-head necrotic area in which transplanted BMSCs incur a great deal of stress apoptosis and aging, which seriously limits transplantation effectiveness [11][12][13] . More and more studies have shown that mitochondrial dysfunction and damaged-mitochondria accumulation occur before cell stress apoptosis and senescence [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after ischemic necrosis of the femoral head, inflammatory cells infiltrate, and the released inflammatory mediators also mediate ROS production by the inflammatory cells. Therefore, after necrosis of the femoral head, a local OS microenvironment forms [8][9][10][11] . In order to further study the effects of OS on BMSCs and then to treat the BMSCs, we used high-concentration H 2 O 2 (1000 μM) to simulate an OS microenvironment 35 .…”
Section: Excessive Accumulation Of Damaged Mitochondria Led To Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, BMSCs have been used in the treatment of various diseases, especially in tissue engineering . However, we have found that the clinical application of BMSCs still has problems that need to be solved: oxidative stress (OS) severely limits the survival of BMSCs after transplantation, and seriously affects the transplantation efficacy . OS can produce excessive reactive oxygen species (ROS) in BMSCs, which can peroxidize DNA, protein, lipid, mitochondria, endoplasmic reticulum, and others, and eventually accelerate cell senescence and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…The PQ + Se@SiO 2 group was also treated with 1 mg/kg porous Se@SiO 2 nanospheres via intraperitoneal injection every 24 h. The concentration of porous Se@SiO 2 nanospheres was selected according to our previous research. 21 The PQ group and PQ + Se@SiO 2 group were randomly divided into 3 sub-groups according to differing times of examination (24,48 and 72 h) after PQ treatment. The rats were executed at the corresponding time points after injection of sodium pentobarbital (50 mg/kg).…”
Section: Animal Experimentsmentioning
confidence: 99%